2009
DOI: 10.1089/neu.2008.0849
|View full text |Cite
|
Sign up to set email alerts
|

Does Traumatic Brain Injury Increase Risk for Substance Abuse?

Abstract: Wars in Afghanistan and Iraq have resulted in thousands of military personnel suffering traumatic brain injury (TBI), including closed-head injuries. Of interest is whether these individuals and other TBI survivors are at increased risk for substance use disorder (SUD). While it has been well established that drug or alcohol intoxication itself increases probability of suffering a TBI in accidents or acts of violence, little is known about whether the brain insult itself increases the likelihood that a previou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(24 citation statements)
references
References 51 publications
0
24
0
Order By: Relevance
“…The need to do so is supported by the finding of a relationship between right MOFC thickness and SES. However, in regards to both socioeconomic status and substance abuse, the directionality of causation when interacting with TBI is unclear (Bjork & Grant, ; Felde, Westermeyer, & Thuras, ; Hoofien, Vakil, Gilboa, Donovick, & Barak, ; Nordstrom, Edin, Lindstrom, & Nordstrom, ; Rassovsky et al., ). Further, the groups were not matched for aggressive behavior; a future study comparing aggression‐matched controls would be valuable to more completely evaluate the relationship between OFC morphometry and aggressive behavior in subjects with and without mTBI.…”
Section: Discussionmentioning
confidence: 99%
“…The need to do so is supported by the finding of a relationship between right MOFC thickness and SES. However, in regards to both socioeconomic status and substance abuse, the directionality of causation when interacting with TBI is unclear (Bjork & Grant, ; Felde, Westermeyer, & Thuras, ; Hoofien, Vakil, Gilboa, Donovick, & Barak, ; Nordstrom, Edin, Lindstrom, & Nordstrom, ; Rassovsky et al., ). Further, the groups were not matched for aggressive behavior; a future study comparing aggression‐matched controls would be valuable to more completely evaluate the relationship between OFC morphometry and aggressive behavior in subjects with and without mTBI.…”
Section: Discussionmentioning
confidence: 99%
“…Traumatic brain injury (TBI) is currently underdiagnosed . Mild TBI may predispose patients to increased substance abuse . Those with head trauma tend to have higher premorbid rates of abuse and addiction which may be the mechanism of the trauma in many cases .…”
Section: Factors Affecting Chronic Painmentioning
confidence: 99%
“…When studying TBI in offender populations, possible confounders of an association between TBI and offending need to be considered. Previous studies have demonstrated an association between TBI and varying symptoms and diagnoses of mental disorders including substance use disorders (SUD), both of which are common in offender populations (2,(21)(22)(23)(24). A systematic review of TBI in prison populations demonstrated that comorbid mental disorders and neurocognitive deficits were more common among offenders with TBI compared to those without TBI (18).…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review of TBI in prison populations demonstrated that comorbid mental disorders and neurocognitive deficits were more common among offenders with TBI compared to those without TBI (18). In particular, SUD needs to be considered in this respect, as an increasing number of studies show that early life TBIs increase the risk of subsequent substance use and other risky behaviors in offender populations, with younger age at TBI being associated with early substance (including alcohol) use (21,22,24). This seems especially important to consider in studies of the association between TBI and aggressive antisocial behaviors, since younger age at onset of substance use increases the total aggression, and there is a well-established association between SUD and violent criminality (22,25,26).…”
Section: Introductionmentioning
confidence: 99%